Analisis Korelasi Keterampilan Komunikasi Ilmiah dan Kolaborasi Siswa SMP pada Pembelajaran IPA - Dalilah Adyanti Putri; Sudarti Sudarti; Rif'ati Dina Handayani (Universitas Indraprasta PGRI, 2026)
This study was motivated by the suboptimal level of students’ scientific communication and collaboration skills in science learning. The purpose of this study was to analyze this relationship. The study was conducted on 46 eighth-grade students at SMP Negeri 1 Wringin. Data were collected using a Likert-scale questionnaire that measured five indicators of scientific communication and five indicators of collaboration. A normality test using the Shapiro–Wilk test showed that the data were normally distributed. Pearson’s correlation analysis yielded a correlation coefficient of 0.678 with a significance level of 0.000. These results indicate a strong and positive relationship between the two skills. Students with better scientific communication skills tend to have higher collaboration skills in science learning. These findings underscore the importance of strengthening scientific communication to improve the effectiveness of group work in the classroom